THE EFFECT OF FINTECH PAYMENT AND FINANCIAL LITERACY ON EMPLOYEES' FINANCIAL BEHAVIOR - Negara, Andi Kusuma; Sunaryo, Dede (Digital Business Journal, 2024)
This research aims to examine and determine the influence of Fintech Payment, Financial Literacy on Employee Financial Behavior partially or simultaneously. The data analysis method used is multiple regression analysis so that the direction and magnitude of the influence of the independent variable on the dependent variable can be clearly depicted. This research used SPSS 22. The research sample consisted of 77 employees at PT Garuda. Sampling using the Slovin formula. The research results show that: 1). Fintech Payment has a positive and significant effect on Employee Financial Behavior; 2). Financial Literacy has a positive and insignificant effect on employee financial behavior and simultaneously has a positive and significant effect.